2021
DOI: 10.18549/pharmpract.2021.1.2206
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and behavior of consumers towards the non-prescription purchase of antibiotics: An insight from a qualitative study from New Delhi, India

Abstract: Background: In Low-and Middle-Income Countries, including India, consumers often purchase antibiotics over-the-counter (OTC) from retail pharmacies. This practice leads to the inappropriate use of antibiotics in the community which is an important driver for the development of antimicrobial resistance. A better understanding of consumers’ views towards this grave public health concern is critical to developing evidence-based intervention programs for awareness among the general population. Objective: To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 41 publications
0
28
0
2
Order By: Relevance
“…The retail pharmacies must have at least one qualified pharmacist to obtain a license. However, most retail pharmacies have unqualified personnel who run the business and dispense medicines, including “OTC antibiotics.” This is a common practice, as reported earlier in a study from New Delhi, India [ 20 , 25 ].…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…The retail pharmacies must have at least one qualified pharmacist to obtain a license. However, most retail pharmacies have unqualified personnel who run the business and dispense medicines, including “OTC antibiotics.” This is a common practice, as reported earlier in a study from New Delhi, India [ 20 , 25 ].…”
Section: Discussionmentioning
confidence: 70%
“…These practices of antibiotic dispensing clearly indicate that retail pharmacies not only flout the rules for dispensing drugs (both Schedule H and H1) without a prescription, but also give antibiotics in cases where they are not required. Earlier studies have indicated that consumers can easily obtain antibiotics without a prescription in LMICs [ 13 , 25 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet reports suggest a degree of confusion among members of the Indian public around some messages in the campaigns conducted to date. 113 Further media campaigns can be pursued on a sustained basis by relevant government agencies; perhaps in conjunction with NGOs and civil society organisations. Techniques and principles used successfully in other countries can also be considered and possibly applied in future campaign designs in India.…”
Section: Novel Regulatory Interventionsmentioning
confidence: 99%